Effect of ketamine on cellular immunity and inflammation in patients who undergo laparoscopic colon cancer surgery: a retrospective study - Ji, Jiajia; Zhang, Haiping; Zhou, Lixia; Fan, Chunlan; Dai, Ligen; Mao, Shaolei (Frontiers in Pharmacology, 2025)
ObjectiveAnesthesia during the surgery impairs immune systems. Ketamine is an anesthetic with immune protective effects. This study intended to investigate the effect of a ketamine-involved anesthetic regimen on cellular immunity and inflammatory cytokines in patients who undergo laparoscopic colon cancer surgery.MethodsThis retrospective study screened 60 patients who underwent laparoscopic colon cancer surgery with an anesthesia regimen involving ketamine (N = 30, ketamine group) or not (N = 30, opioid group). Data on surgery-related parameters, blood pressure, heart rate (HR), blood routine examination parameters, cluster of differentiation (CD) 3+ and CD4+ T cells, inflammatory cytokines, and adverse reactions were retrieved. Time points were defined as entering the operating room (T1), 5 min after anesthetic induction (T2), the end of surgery (T3), and 24 h after surgery (T4).ResultsThe 1 h-postoperative pain score (P < 0.001) and length of stay (P < 0.001) were lower in ketamine group than in opioid group. Blood pressure and HR from T1 to T4 were more stable in ketamine group than in opioid group. Neutrophils (P < 0.001), CD3+ (P < 0.001) and CD4+ T cells (P = 0.002) at T4 were higher in ketamine group than in opioid group. Interleukin (IL)-10 at T3 (P < 0.001) and T4 (P < 0.001) were higher, while IL-6 at T3 (P < 0.001) and T4 (P < 0.001) were lower in ketamine group than in opioid group. There was no discrepancy in incidences of adverse reactions between groups.ConclusionA ketamine-involved anesthetic regimen seems to be correlated with the improvement of cellular immunity and inflammation with a tolerable safety profile. However, more studies with a prospective, randomized, controlled design are needed to verify this finding and draw a solid conclusion.